2022
DOI: 10.1109/tvt.2022.3152980
|View full text |Cite
|
Sign up to set email alerts
|

Perception of Driving Simulations: Can the Level of Detail of Virtual Scenarios Affect the Driver's Behavior and Emotions?

Abstract: Human factors studies are becoming more and more crucial in the automotive sector due to the need to evaluate the driver's reactions to the increasingly sophisticated drivingassistant technologies. Driving simulators allow performing this kind of study in a controlled and safe environment. However, the driving simulation's Level of Detail (LOD) can affect the users' perception of driving scenarios and make an experimental campaign's outcomes unreliable. This paper proposes a study investigating possible correl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 71 publications
(85 reference statements)
0
6
0
Order By: Relevance
“…Himmels et al [20] compared the perceived realism of lower-and higher-fidelity simulators, and found that the latter, which had a full-vehicle mockup with a 360-degree field of view, achieved higher perceived realism than the former, which had a full-vehicle mockup with a 180-degree field of view. By contrast, Shi et al [21] manipulated a driving scenario that changed the details of buildings and surrounding environment to investigate the differences in perceived realism and found no significant effect of these details of VR scenarios. Finally, recent research investigating the influences of external factors on perceived realism in VR driving simulations includes the study by Colley et al [22], who found that swivel seat rotation increased perceived realism.…”
Section: A Related Work On Perceived Realism In Vr Driving Simulationsmentioning
confidence: 98%
“…Himmels et al [20] compared the perceived realism of lower-and higher-fidelity simulators, and found that the latter, which had a full-vehicle mockup with a 360-degree field of view, achieved higher perceived realism than the former, which had a full-vehicle mockup with a 180-degree field of view. By contrast, Shi et al [21] manipulated a driving scenario that changed the details of buildings and surrounding environment to investigate the differences in perceived realism and found no significant effect of these details of VR scenarios. Finally, recent research investigating the influences of external factors on perceived realism in VR driving simulations includes the study by Colley et al [22], who found that swivel seat rotation increased perceived realism.…”
Section: A Related Work On Perceived Realism In Vr Driving Simulationsmentioning
confidence: 98%
“…In such a perspective, it is crucial selecting the adequate constructs [12] and related tools depending on the goal, be it an investigation of the existing condition [13] or the assessment of a design proposal [14,15]. Emotions are one of the most investigated constructs describing the subjective reaction to a given environment [16], applied, for example, to commercial settings [17,18] or mobility experience [19][20][21]. The place experience can be described also referring to the cognitive dimension, for example, considering the balance between a good understanding of a place and the attraction to further explore it as an indicator of preferred environments [22].…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…In all of these developments, the most important factor that manufacturers try to optimize is the driving experience evaluated by the driver. Driving experience is a multidimensional construct [1][2][3] , which from a human factor's perspective is shaped by many different aspects, including driving performance 4 , driving experience 5 , age 5,6 , personality traits 5 , as well as fatigue 7 , emotions 8 , behaviors 8 , and intention 9 . Importantly, however, the first step for any of these aspects consists of the various perceptual inputs generated by the driving environment and processed via the different sensory modalities.…”
Section: Failure To Integrate? Investigating Multisensory Acceleratio...mentioning
confidence: 99%
“…As examples, Braun 5 have tried to optimize in-car visual information systems for automotive user interfaces using perceptual principles. In the context of driving simulations, Shi 8 measured driving performance, physiological data, subjective evaluations, and emotional states depending on the visual level of detail of the simulation, showing that visual fidelity, indeed, has a broad impact on the driving experience. One of the earliest studies investigating acceleration perception is that of Rockwell and Snider, who determined the absolute threshold of linear acceleration for linear acceleration with automotive vehicles to between 0.01 and 0.02g 24 .…”
Section: Related Workmentioning
confidence: 99%